2018
DOI: 10.4049/jimmunol.1700796
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Peroxiredoxin 1 by a Curcumin Analogue, AI-44, Inhibits NLRP3 Inflammasome Activation and Attenuates Lipopolysaccharide-Induced Sepsis in Mice

Abstract: Aberrant activation of the NLRP3 inflammasome contributes to the onset and progression of various inflammatory diseases, making it a highly desirable drug target. In this study, we screened a series of small compounds with anti-inflammatory activities and identified a novel NLRP3 inflammasome inhibitor, AI-44, a curcumin analogue that selectively inhibited signal 2 but not signal 1 of NLRP3 inflammasome activation. We demonstrated that AI-44 bound to peroxiredoxin 1 (PRDX1) and promoted the interaction of PRDX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Our current results are strongly supportive of the validity of this approach by showing that genetic silencing of PRDX1 in TNBC cell lines amplifies the efficacy of one of the most promising prooxidant approaches, i.e., the combination of Asc and Men (Figure 3 and Figure S5D,E). The difficulty of PRDX1 targeting in cancer in the clinical settings is related to the fact that chemical agents known to inhibit PRDX1, such as adenanthin [34,43], AI-44 [44], or frenolicin B [45], or the PRDX1-related antioxidant enzymatic system, such as SK053 [14] or AUR [13], are in most cases fairly unselective and/or do not possess satisfactory pharmacokinetics. The exception for the latter is AUR, the clinically approved drug primarily used in rheumatology and suggested in numerous other indications [46].…”
Section: Discussionmentioning
confidence: 99%
“…Our current results are strongly supportive of the validity of this approach by showing that genetic silencing of PRDX1 in TNBC cell lines amplifies the efficacy of one of the most promising prooxidant approaches, i.e., the combination of Asc and Men (Figure 3 and Figure S5D,E). The difficulty of PRDX1 targeting in cancer in the clinical settings is related to the fact that chemical agents known to inhibit PRDX1, such as adenanthin [34,43], AI-44 [44], or frenolicin B [45], or the PRDX1-related antioxidant enzymatic system, such as SK053 [14] or AUR [13], are in most cases fairly unselective and/or do not possess satisfactory pharmacokinetics. The exception for the latter is AUR, the clinically approved drug primarily used in rheumatology and suggested in numerous other indications [46].…”
Section: Discussionmentioning
confidence: 99%
“…Different regulators may positively modulate NLRP3 inflammasome such as DDX3X, GBP5 and cathepsin, thus inducing NLRP3 oligomerization and promoting ASC assembly [ 89 , 90 , 91 ]. On the other hand, HSP70, PRDX1, NLRC3, SHP and POPs may negatively modulate NLRP3 assembly, acting on NLRP3 itself or inhibiting the formation of NLRP3/ASC complex or the interaction between ASC and procaspase-1 [ 92 , 93 , 94 , 95 , 96 ]. Post-translational modification may also promote NLRP3 assembly and interaction, in fact, the dephosphorylation of pyrin domain mediated by PP2A significantly inhibited NLRP3 inflammasome activation thus blocking ASC assembly that requires pyrin domain (PYD)–PYD interactions [ 97 ].…”
Section: Nlrp3 Inflammasome Regulationmentioning
confidence: 99%
“…Although Prdx1, an RBP (Baltz et al, 2012;Castello et al, 2012;Kim et al, 2012;Kwon et al, 2013;Sebestyén et al, 2016), has been shown to be elevated after ICH (Nakaso et al, 2000), its roles in brain injury after ICH are still largely unknown. Prdx1 is a member of the peroxiredoxin family (Wood et al, 2003) and has been shown to be involved in regulating many pathological processes, such as redox reactions (Yamaguchi et al, 1993), inflammatory responses, apoptosis (Liu et al, 2014(Liu et al, , 2018Min et al, 2018;Lu et al, 2019), and tumorigenesis (Hoshino et al, 2005;Cao et al, 2009). These findings suggest that Prdx1 may also play important roles in regulating the above-mentioned pathological processes to influence the brain injury caused by ICH.…”
Section: Introductionmentioning
confidence: 94%